Analisis Rasio Likuiditas, Aktivitas, Solvabilitas Dan Profitabilitas Dalam Mengukur Kinerja Keuangan Pada Perusahan Kontruksi Periode 2020-2022 - Tiara Marcella Ruskito; Tasya Nurhalyza; Viona Eka Putri Mardiono; Nelya Arofatin; Yaohan Ad’nnia Jannah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the financial performance of five leading construction companies in Indonesia, namely PT Wika, PT WASKITA, PT ADHI, PT ACST, and PT JKON, during the period 2020-2022. The dynamic business context, especially in the construction sector, marks the importance of financial performance as an assessment of a company's sustainability and competitiveness. In the face of challenges, including the impact of the global pandemic, financial ratio analysis becomes a key instrument to measure a company's ability to deal with uncertainty.